2019
DOI: 10.1021/acs.analchem.9b01838
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Ion Mobility-Mass Spectrometry System

Abstract: Improvements in the performance and availability of commercial instrumentation have made ion mobility-mass spectrometry (IM-MS) an increasingly popular approach for the structural analysis of ionic species as well as for separation of complex mixtures. Here, a new research instrument is presented which enables complex experiments, extending the current scope of IM technology. The instrument is based on a Waters SYNAPT G2-Si IM-MS platform, with the IM separation region modified to accept a cyclic ion mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
578
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 388 publications
(589 citation statements)
references
References 62 publications
9
578
1
1
Order By: Relevance
“…The relationship between resolving power and path length was further explored to determine the conditions necessary to separate the partially resolved Cm and m 3 C components. After submitting the methyl‐cytidine mixture to 10 passes in the cIM separator (Figure j), the fully resolved m 5 C and m 4 C species were ejected from the device to prevent possible “wrap‐around” effects produced by faster ion populations overtaking slower ones that completed fewer passes . In contrast, the remaining Cm and m 3 C were submitted to additional passes under exactly the same experimental conditions (Figure ).…”
Section: Resultssupporting
confidence: 39%
See 3 more Smart Citations
“…The relationship between resolving power and path length was further explored to determine the conditions necessary to separate the partially resolved Cm and m 3 C components. After submitting the methyl‐cytidine mixture to 10 passes in the cIM separator (Figure j), the fully resolved m 5 C and m 4 C species were ejected from the device to prevent possible “wrap‐around” effects produced by faster ion populations overtaking slower ones that completed fewer passes . In contrast, the remaining Cm and m 3 C were submitted to additional passes under exactly the same experimental conditions (Figure ).…”
Section: Resultssupporting
confidence: 39%
“…This treatment revealed that single‐pass cIM analysis could already improve resolving power by an average ~20% over linear TW device. The corresponding R values obtained after two and three passes are close to the expected square root relationship between R and path length . Interestingly, plots of rCCS versus arrival time reveal systematic deviations from the expected power law model.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…These larger R p values better-reflect the analytical selectivity of TWIMS, with a corresponding low percent error predicted by eqn 5. Conversion to CCS-based R p is also necessary for the recently developed cyclic TWIMS 4,47 (Point L) which indicates that this device operates with a resolving power of ca. 480 for 50 cycles (c.f., Table S1).…”
Section: Resultsmentioning
confidence: 99%